The role of humans, climate and vegetation in the complex fire regimes of north-east Namibia - Humphrey, Glynis (Department of Biological Sciences, 2019)
This thesis explores how interactions and feedbacks between environmental and socio-historical factors influenced fire management dynamics in north-east Namibia. Fires are mostly human ignited, but precipitation patterns influence when and where fires can occur, and there are feedbacks between fire, climate and vegetation cover. Yet, knowledge of historical and contemporary use of fire by societies is fragmented in southern Africa, and is therefore disputed. As a result, the complex interaction between climate, vegetation and human factors that influence fire dynamics remains poorly understood. This thesis explores how the political history, livelihoods, land-use practices, policy changes, vegetation and climatic variation are relevant to present-day fire regimes and management. The study is located in Bwabwata National Park (BNP), north-eastern Namibia, which is managed for both conservation objectives and people’s livelihoods. The park is inhabited by the Khwe (San), former hunter-gatherers, who have been using fire for millennia, and the Bantu-speaking Mbukushu people, who are agriculturalists and pastoralists. The area has been subject to colonial regimes, war, inter-ethnic conflict, social-political resettlement, conservation and associated changing fire management approaches since the 19th century. The vegetation includes omiramba grasslands, savanna-woodlands, Burkea shrublands and riparian types. For this study, qualitative semi-structured interviews with Namibian stakeholders, in combination with multi-year (2000 – 2015) remote sensing products, were used to understand the past and present fire regime characteristics. Interviews with community stakeholders revealed that the Khwe and Mbukushu communities use fire for a diverse range of livelihood activities. Specifically, early season burning is used to assist in hunting, tracking and gathering of veld foods, and for improving forage for livestock. The traditional practice of early season burning is not only culturally and ecologically significant, but has positive consequences for Bwabwata National Park’s conservation objectives, and fire policies, in terms of suppressing late season fires. However, explicit marginalisation of the Khwe since the C19th due to colonial regimes and cross-border wars has disrupted traditional fire management. Interviews with government and conservation stakeholders revealed recognition of the benefits of early season burning for biodiversity. Furthermore, despite the complex social-ecological history of the area, recent policy changes reveal an emerging willingness to incorporate traditional fire management into fire management policy. Moderate Resolution Imaging Spectrometer (MODIS) data was used to analyse the fire regime (burned area, fire frequency, fire number and size, intensity, and seasonality), together with climate (El Niño Southern-Oscillation [ENSO] events; local rainfall patterns) and vegetation data in multiple use (inhabited) and core conservation areas, over a time period that covered a shift in policy from fire suppression (2000-2005) to early season burning (2006-2015). Results from the analysis of the MODIS data revealed that a high frequency of early season burning in the inhabited areas of the park reduced the late season fires and dampened the local rainfall and burned area relationship. Nonetheless, grass growth (i.e. available biomass) during ENSO wet season events (La Niña) resulted in greater area burned and fire sizes in above average rainfall years in the early dry season in the community inhabited areas. In contrast, higher fire intensity and larger fire sizes were evident in the conservation core areas where people were not actively burning. Fire frequencies and burned areas were highest in the omiramba grasslands and savanna-woodlands, in the early dry season under the early burning policy in the east of the park, which reduced fire intensities in these vegetation types. In contrast, burning in the Burkea shrublands was frequent in the late dry season, at higher intensities in the Western conservation area under both policy phases. This study indicates that burned area depends on rainfall, ignitions and fire sizes in inhabited landscapes, where people practice early burning, which has consequences for decreasing the intensity and therefore spread and impact of fires on vegetation. This study highlights the complex interactions between people, rainfall seasonality and fuel availability, as well as the need to incorporate historical factors. The study uses a pyrogeographic framework to integrate the social-cultural, climatic-biological, and topographic-environmental factors with fire. The synthesis reveals that the park communities are currently socially and ecologically vulnerable to global environmental change, given their dependence on fire for ecosystem services. However, the study also highlights how traditional fire management, and specifically early season burning, improves food security and contributes to livelihood subsistence and biodiversity conservation in the park. BNP is characterised by complex historical and present-day social-ecological fire dynamics. The study highlights the importance of understanding the historical and political context of fire for determining and managing current spatial-temporal fire patterns. Respect for diverse fire knowledge and culture, communication and shared governance are central to improving community livelihoods and fire management strategies in BNP. Specifically, the shared interest in early season burning provides a point of confluence between diverse stakeholders in BNP and a basis for fire management policies that benefit biodiversity as well as livelihoods.